An approach to the captive driver in the context of the 15-minute city. The case of Astigarraga - Gortazar-Balerdi, Ander; Markusiewicz, Jacek (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
One of the greatest challenges of the contemporary city in the context of energy transformation is that of sustainable mobility, an issue marked by the dichotomy between the city centre and its periphery, among others. This article exposes the case study of a project the authors carried out in their professional practice in RAZ: an analysis of wage labour-related commuting in the municipality of Astigarraga, Gipuzkoa, conducted as part of the municipality's sustainable urban mobility plan. The case study shows the inherent difficulties of contemporary metropolitan mobility dynamics, and helps to draw the profile of the captive driver of the private car. We carried out the analysis using methodologies based on data analysis, visualization or simulation, which illustrate the opportunities that this type of methodologies offers, also in the field of sustainable mobility.
Keywords: mobility; data visualization; interfaces; captive driver; sustainability